1990
DOI: 10.1111/j.1464-5491.1990.tb01419.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Muscle Performance in Patients with Type 1 Diabetes

Abstract: Respiratory muscle strength and endurance were examined in 31 Type 1 diabetic patients and in age, sex, and weight matched control subjects. No significant difference in respiratory muscle strength was noted between the two groups. Maximal static inspiratory pressure was 92.3 +/- 33.9 (+/- SD) and 99.5 +/- 23.0% of the predicted values in the patient and control groups, respectively. Maximal static expiratory pressures were 75.1 +/- 14.3 and 77.4 +/- 14.0% of the predicted values in the patient and control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 19 publications
4
17
0
3
Order By: Relevance
“…Interestingly, all results from volitional tests were comparable in diabetic patients and controls, indicating that global respiratory neuromuscular function is preserved in these patients. This is in line with previous studies [9] and supports the clinical observation that chronic respiratory failure caused by respiratory muscle weakness is unlikely in diabetic patients [33]. However, Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, all results from volitional tests were comparable in diabetic patients and controls, indicating that global respiratory neuromuscular function is preserved in these patients. This is in line with previous studies [9] and supports the clinical observation that chronic respiratory failure caused by respiratory muscle weakness is unlikely in diabetic patients [33]. However, Fig.…”
Section: Discussionsupporting
confidence: 93%
“…To date, no human studies on respiratory neuromuscular function have provided clear evidence of respiratory neuromuscular involvement in diabetic patients, since only volitional tests were used in the few previous studies [9][10][11]. However, volitional tests on respiratory neuromuscular function are highly variable due to their dependency on the participant making a truly maximal effort.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the levels of respiratory muscle strength have been found to be generally low [48][49][50]. A recent study with type 2 diabetic patients showed a modest reduction in respiratory muscle strength, inversely correlated to the degree of metabolic control, expressed by the HbA1c level [51].…”
Section: Respiratory Muscle Function Testingmentioning
confidence: 99%
“…Penjelasan yang mungkin terhadap penurunan FVC adalah penurunan fungsi otot-otot pernapasan yang menghalangi ekspirasi selama manuver aliran volume. 32 Elastisitas alveolus yang terganggu juga dapat digambarkan dengan penurunan FVC. Pada saat awal awitan DM, mekanisme adaptif dari sistem respiratorik membuat pertahanan sampai stabil dalam beberapa tahun.…”
Section: Pembahasanunclassified